Proposals for improving the classification of land purpose types (on the example of the category of residential and public building lands) - Dorosh, Y.; Dorosh, O.; Tarnopolskyi, A.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2022)
The current classification of land uses for residential and public development was analyzed and proved to be in need of improvement. Proposals for its improvement within the researched category of land based on current land legislation and other normative legal acts are given. It has been proven that the existing list of the main types of land plots (which are based on the content of Article 38 of the Land Code of Ukraine) in the current classification is incomplete and not fully justified. Examples of unjustified assignment of land plots of other land categories to the category of land for residential and public development were revealed. In accordance with this, a 4-level structure of the classification of types of land use for residential and public development is proposed. Taking into account the military aggression of the Russian Federation against Ukraine, it is currently impossible to use part of the land plots for their main purpose. From these positions, it is proposed to additionally highlight "technologically polluted lands as a result of hostilities" within the framework of the above-mentioned classifier. And after carrying out appropriate works on demining and reclamation of these lands to their safe use for people and the environment, they can be returned to use for the main purpose. Keywords: classification of types of purpose land, land for residential and public development, man-made contaminated land due to hostilities.